49,XXXXY syndrome: behavioural and developmental profiles. - Lomelino, C A (1991)
Behavioural, psychological, and cognitive profiles of three cases, including a 5 year old male with a 49,XXXXY karyotype and a (3;15) translocation, a 9 year old male with a 49,XXXXY karyotype, and a 32 year old male with 48,XXXY/49,XXXXY mosaicism, are presented. Significant behavioural problems were seen in the two older patients. The degree of mental retardation and impairment of language abilities were shown to be more severe in the older subjects as well. These findings are discussed with respect to the effects of the X chromosome on brain development.